A finite time composite control method for quadrotor UAV with wind disturbance rejection. (October 2022) - Li, Shenghui; Sun, Zhenxing; Talpur, Mashooque Ali
Abstract: The quadrotor UAV is subject to wind disturbance during flight, which causes attitude deviation and oscillation. To improve anti-wind disturbance performance, this work offers a reduced-order generalized proportional–integral observer-based wind-disturbance control strategy for quad-rotor UAVs (RGPIO). To improve the disturbance rejection property of quadrotor UAV systems, this work offers a composite control approach based on reduced-order generalized proportional–integral observer (RGPIO) and nonsmooth control. To begin, an RGPIO is used to evaluate system disruptions. In the feed-forward compensation scheme, the anticipated value is used. Second, the feedback design employs a nonsmooth feedback control method. The controller's stability is then checked. When compared to the standard PID control technique, the experimental findings show that the suggested control method successfully suppresses the wind disturbance.